Carbonation study in a cement matrix with carbon nanotubes (2019)
Carbon nanotubes as additions in Portland cement based matrices have a great potential to improve the mechanical properties of mortars and concretes; however, little work has been done regarding the effect that they have on the chemical durability of the cement matrix and reinforcing steel. In this work, carbon nanotubes are dispersed in water solution with Triton X 100 surfactant and blended in Portland cement mortars. A sharp decrease in compression resistance was observed at all curing ages (7, 14, 21 and 28 days) while a depth increase in the carbonation profile was found, which is associated with a decrease in the matrix durability. © Published under licence by IOP Publishing Ltd.